2015
DOI: 10.1111/anae.13344
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate dosing of sugammadex to reverse deep rocuronium-induced neuromuscular blockade in morbidly obese patients

Abstract: SummaryIn morbidly obese patients, the speed of reversal of neuromuscular blockade with sugammadex based on ideal body weight is still matter of debate. In this single-center, randomised, double-blinded study, neuromuscular blockade was monitored in 50 patients using acceleromyography at the adductor pollicis. At the end of surgery with deep rocuronium-induced neuromuscular blockade, patients randomly received sugammadex 4 mg.kg À1 (high dose group), 2 mg.kg À1 (middle dose group), or 1 mg.kg À1 (low dose grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 37 publications
1
20
0
1
Order By: Relevance
“…At the end of surgery, a moderate NMB was reversed with sugammadex (MSD BV, Haarlem, The Netherlands) 2 mg/kg ideal body weight, while a deep NMB was reversed with sugammadex 4 mg/kg ideal body weight [5]. The endotracheal tube was removed when the TOF-ratio > 0.9 and the patient breathed spontaneously and was fully awake.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of surgery, a moderate NMB was reversed with sugammadex (MSD BV, Haarlem, The Netherlands) 2 mg/kg ideal body weight, while a deep NMB was reversed with sugammadex 4 mg/kg ideal body weight [5]. The endotracheal tube was removed when the TOF-ratio > 0.9 and the patient breathed spontaneously and was fully awake.…”
Section: Methodsmentioning
confidence: 99%
“…We thank Dr. Carron for his interest in our paper . Among studies that reported a mean reversal time following sugammadex shorter than our results, two were undertaken in non‐obese patients.…”
mentioning
confidence: 74%
“…This substance is used in adults of normal weight at 2mg/kg to promote reversion of moderate NMB, measured by the train-of-four (TOF) stimulus sequence (T4/T1 ≥0.9); at 4mg/kg for reversal of deep NMB; and at a dose of 16mg/kg for immediate reversal of rocuronium-induced NMB [9][10][11][12][13] . Previous studies have suggested that reversal of NMB in morbidly obese patients could be achieved at 4mg/kg for deep blockade considering the ideal body weight, or 2mg/kg, regardless of which body weight is considered, ideal or actual 18,19 .…”
Section: Introductionmentioning
confidence: 99%